2012
DOI: 10.1007/s12665-012-1921-7
|View full text |Cite
|
Sign up to set email alerts
|

Dolomitic slates from Uruguay: petrophysical and petromechanical characterization and deposit evaluation

Abstract: Slates are internationally known as roof and façade-cladding material since prehistoric times. The methods required to mine and manufacture these dimensional stones are relatively simple in comparison to those utilized in granitic dimensional stones. This has led to a worldwide rentable commercialization of slate in the last centuries and also to the development of characteristic cultural landscapes. In Uruguay several slates are mined and used in architecture, especially as façade cladding and floor slabs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Other authors cited such norm calculations together with results of other analyses and found good matches [9]. The results of more than 20 years of application of "slatenorm" [6,9,10,[12][13][14][15] have shown that the inclusion of additional ore minerals, color-giving minerals, and hydro-micas (especially illite) in the new slatecalculation is reasonable.…”
Section: Therein)mentioning
confidence: 89%
See 2 more Smart Citations
“…Other authors cited such norm calculations together with results of other analyses and found good matches [9]. The results of more than 20 years of application of "slatenorm" [6,9,10,[12][13][14][15] have shown that the inclusion of additional ore minerals, color-giving minerals, and hydro-micas (especially illite) in the new slatecalculation is reasonable.…”
Section: Therein)mentioning
confidence: 89%
“…The geological information of the slate samples analyzed in this paper (also based on[4,6,9,12,14,15,18,24]. Cont.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Iron sulphides such as pyrite and pyrrhotite, as well as the carbonates can be the most damaging group of minerals in terms of the integrity of any slate [72,73]. For example, a slate containing coarse-grained pyrite as inclusions, is not very stable against temperature changes, due to the difference in thermal expansion among the rock constituents [74]. Iron sulphide oxidation also produces red staining that affects the tile surface and the other tiles below.…”
Section: Slatesmentioning
confidence: 99%
“…One aspect usually neglected during the analyses of the joint spacing is the distribution of the data, which usually follows a lognormal distribution (Priest 1993;Sousa 2010;Annavarapu et al 2012;Sousa et al 2016;Santos et al 2018;Ferrari et al 2019;Bruzzi et al 2020). Consequently, the mean value is not the best measure of the "average" distance or block volume, being preferable a more realistic value as the median value (Sousa 2010;Morales Demarco et al 2013). Using median values, the results of the block size and quarry yield will be more conservative (Morales Demarco et al 2013) and closer to the reality.…”
Section: Introductionmentioning
confidence: 99%